2012
DOI: 10.1073/pnas.1114422109
|View full text |Cite
|
Sign up to set email alerts
|

Phasic D1 and tonic D2 dopamine receptor signaling double dissociate the motivational effects of acute nicotine and chronic nicotine withdrawal

Abstract: Nicotine, the main psychoactive ingredient of tobacco smoke, induces negative motivational symptoms during withdrawal that contribute to relapse in dependent individuals. The neurobiological mechanisms underlying how the brain signals nicotine withdrawal remain poorly understood. Using electrophysiological, genetic, pharmacological, and behavioral methods, we demonstrate that tonic but not phasic activity is reduced during nicotine withdrawal in ventral tegmental area dopamine (DA) neurons, and that this patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
84
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(95 citation statements)
references
References 49 publications
11
84
0
Order By: Relevance
“…This phasic/tonic dopamine signaling ratio increase, as observed during withdrawal in previous studies (Grieder et al, 2012;Zhang et al, 2012), is implicated in habit learning (Aggarwal and Wickens, 2011), enhanced reward association and acquisition of incentive salience (Grieder et al, 2012). Thus, these studies might further explain the greater motivation to seek a reward, whether it is an electric stimulation or a substance of abuse, both observed here by the use of ICSS and CPP and the latter in a recent study by Cohen et al (2012), or the enhanced cue association, observed by Scott and Hiroi (2010), during withdrawal.…”
Section: Discussionsupporting
confidence: 62%
“…This phasic/tonic dopamine signaling ratio increase, as observed during withdrawal in previous studies (Grieder et al, 2012;Zhang et al, 2012), is implicated in habit learning (Aggarwal and Wickens, 2011), enhanced reward association and acquisition of incentive salience (Grieder et al, 2012). Thus, these studies might further explain the greater motivation to seek a reward, whether it is an electric stimulation or a substance of abuse, both observed here by the use of ICSS and CPP and the latter in a recent study by Cohen et al (2012), or the enhanced cue association, observed by Scott and Hiroi (2010), during withdrawal.…”
Section: Discussionsupporting
confidence: 62%
“…This previously unreported finding is of particular interest as numerous animal studies have suggested that the dysphoric effects associated with withdrawal could be DAmediated (Grieder et al, 2012), and this study provides evidence for such a relationship in humans. We also found that while the total puff volume correlated with the craving and not [ 11 C]-( þ )-PHNO binding, the number of puffs subjects made during the smoking condition did correlate with both DA level elevation in LST and decrease in urge to smoke.…”
Section: (C) Expectancy Factor (Tobacco Craving Questionnaire Tcq)mentioning
confidence: 72%
“…Therefore, the role of DA in nicotine addiction still remains unclear (refer to the study by Le Foll et al (2009a) for a review). While some authors agree that DA signaling at the D2/3 receptor appears to mediate the rewarding and motivational effects of nicotine, other have argued that DA may instead mediate aversion to acute nicotine or nicotine withdrawal (Grieder et al, 2012;Laviolette and Van Der Kooy, 2003a, b). Because of this complexity, it appears that the use of smoking topography to characterize smoking behavior may yield valuable insights, as rate of nicotine administration or latency to drug-use are critically related to drug reinforcements and warrants further study.…”
Section: Introductionmentioning
confidence: 99%
“…Screening of two independent clinical populations revealed that CB 1 gene variants are associated with nicotine dependence (Chen et al, 2008) and the CB 1 receptor antagonist Rimonabant (SR141716A) prolonged abstinence rates in smokers expressing motivation to quit . SR141716A and the related CB 1 antagonist AM251 reduce nicotine selfadministration (SA) by rats (Cohen et al, 2002(Cohen et al, , 2005Forget et al, 2009;Shoaib, 2008), attenuate nicotine-induced increases in nucleus accumbens (NAc) dopamine (DA) (Cheer et al, 2007;Cohen et al, 2002;Grieder et al, 2012), and reduce reinstatement of nicotine-seeking behavior in animal models of relapse (Forget et al, 2009). Collectively, these findings provide strong evidence for a CB 1 receptor involvement in the motivational effects produced by nicotine, and imply a role for endocannabinoid (eCB) signaling in this process.…”
Section: Introductionmentioning
confidence: 81%